Nature's Power and Human Vulnerability in Saki’s The Interlopers: An Ecocritical Approach - Adilla Paradiba; Nurul Amelia; Dinda Tanjung; Dela Pebriani; Purwarno Purwarno (International Journal of English and Applied Linguistics (IJEAL), 2024)
This research employed the lens of ecocriticism, which explored the intricate relationship between humans, culture, and the environment depicted in the novel. Through a qualitative descriptive approach, this research delved into the narrative intricacies of The Interlopers, emphasizing the insignificance of human conflicts in the face of nature's might. By advocating for an ecocritical perspective, the study aimed to promote awareness of environmental issues and advocate for more sustainable and ethical interactions with nature. Through a comprehensive literature review, the paper situated The Interlopers within the broader context of ecocritical discourse, elucidating its contribution to understanding the complexities of human-nature relationships in literature. Ultimately, this research shed light on the profound implications of human actions on the environment, urging for a paradigm shift towards greater harmony and stewardship of nature. The research showed the power dynamics between humanity and nature, revealing how human greed and hostility interacted with the formidable forces of the natural world. Furthermore, it underscored the evolution of enmity between conflicting parties, highlighting the detrimental consequences of perpetual feuds fueled by arrogance and territorial disputes.